The mobile gene cassette carrying tetracycline resistance genes in Aeromonas veronii strain Ah5S-24 isolated from catfish pond sediments shows similarity with a cassette found in other environmental and foodborne bacteria - Dubey, Saurabh; Ager-Wiick, Eirill; Peng, Bo; DePaola, Angelo; Sørum, Henning; Munang’andu, Hetron Mweemba (Frontiers in Microbiology, 2023)
Aeromonas veronii is a Gram-negative bacterium ubiquitously found in aquatic environments. It is a foodborne pathogen that causes diarrhea in humans and hemorrhagic septicemia in fish. In the present study, we used whole-genome sequencing (WGS) to evaluate the presence of antimicrobial resistance (AMR) and virulence genes found in A. veronii Ah5S-24 isolated from catfish pond sediments in South-East, United States. We found cphA4, dfrA3, mcr-7.1, valF, blaFOX-7, and blaOXA-12 resistance genes encoded in the chromosome of A. veronii Ah5S-24. We also found the tetracycline tet(E) and tetR genes placed next to the IS5/IS1182 transposase, integrase, and hypothetical proteins that formed as a genetic structure or transposon designated as IS5/IS1182/hp/tet(E)/tetR/hp. BLAST analysis showed that a similar mobile gene cassette (MGC) existed in chromosomes of other bacteria species such as Vibrio parahaemolyticus isolated from retail fish at markets, Aeromonas caviae from human stool and Aeromonas media from a sewage bioreactor. In addition, the IS5/IS1182/hp/tet(E)/tetR/hp cassette was also found in the plasmid of Vibrio alginolyticus isolated from shrimp. As for virulence genes, we found the tap type IV pili (tapA and tapY), polar flagellae (flgA and flgN), lateral flagellae (ifgA and IfgL), and fimbriae (pefC and pefD) genes responsible for motility and adherence. We also found the hemolysin genes (hylII, hylA, and TSH), aerA toxin, biofilm formation, and quorum sensing (LuxS, mshA, and mshQ) genes. However, there were no MGCs encoding virulence genes found in A. veronii AhS5-24. Thus, our findings show that MGCs could play a vital role in the spread of AMR genes between chromosomes and plasmids among bacteria in aquatic environments. Overall, our findings are suggesting that MGCs encoding AMR genes could play a vital role in the spread of resistance acquired from high usage of antimicrobials in aquaculture to animals and humans.